Keterlambatan Bicara pada Anak: Pendekatan Evidence-Based dalam Evaluasi dan Penatalaksanaan (Laporan Kasus) - Aty Firsiyanti; Gina Noor Djalilah; Yusian Eri Fitria; Mufidah Hariani; Adristy Anneira Vanka Meisya; Nabilah Isyraq Syahirah; Farida Kholifah; Salsabila Rayhani; Zetty Fortune Ananta Mulia (Universitas Muhammadiyah Surabaya, 2026)
Speech delay is one of the most common developmental disorders in children and may affect communication, social interaction, and overall development. This case report describes a 33-month-old boy with delayed speech development. His parents reported that the child was unable to speak according to his age and could only say one meaningful word. The delay was first noticed at 16 months of age. Despite delayed expressive language, the patient still demonstrated relatively good receptive language abilities, including understanding simple commands, responding when called, and communicating through gestures with good eye contact. Developmental history revealed delayed motor milestones, including sitting independently at 11-12 months, crawling at 13-15 months, and walking independently at 17-18 months. Several risk factors were identified, including neonatal asphyxia requiring NICU admission, formula feeding since birth, excessive screen time exposure, limited verbal stimulation, minimal interaction with peers, and a family history of delayed speech. The patient underwent speech therapy and occupational therapy for approximately eight months. Early identification and multidisciplinary intervention are important to improve communication and developmental outcomes in children with speech delay.